Pathogenesis of Acute Respiratory Distress Syndrome - Huppert, Laura A.; Matthay, Michael A.; Ware, Lorraine B. (Seminars in Respiratory and Critical Care Medicine, 2019)
Acute respiratory distress syndrome (ARDS) is a syndrome of acute respiratory failure caused by noncardiogenic pulmonary edema. Despite five decades of basic and clinical research, there is still no effective pharmacotherapy for this condition and the treatment remains primarily supportive. It is critical to study the molecular and physiologic mechanisms that cause ARDS to improve our understanding of this syndrome and reduce mortality. The goal of this review is to describe our current understanding of the pathogenesis and pathophysiology of ARDS. First, we will describe how pulmonary edema fluid accumulates in ARDS due to lung inflammation and increased alveolar endothelial and epithelial permeabilities. Next, we will review how pulmonary edema fluid is normally cleared in the uninjured lung, and describe how these pathways are disrupted in ARDS. Finally, we will explain how clinical trials and preclinical studies of novel therapeutic agents have further refined our understanding of this condition, highlighting, in particular, the study of mesenchymal stromal cells in the treatment of ARDS.
Keywords: acute respiratory distress syndrome; alveolar fluid clearance; vectorial ion transport; pulmonary edema; mesenchymal stromal cells